Effects of aftercrop tomato and maize on the soil microenvironment and microbial diversity in a long-term cotton continuous cropping field - Han, Shouyan; Ji, Xiaohui; Huang, Liwen; Liu, Gaijie; Ye, Jingyi; Wang, Aiying (Frontiers in Microbiology, 2024)
Long-term continuous cropping affects the soil microecological community and leads to nutrient imbalances, which reduces crop yields, and crop rotation can increase soil productivity. To study the effects of the cultivation of tomato (Solanum lycopersicum) and corn (Zea mays) on the microbial community, physical and chemical factors and the structure of aggregates in cotton (Gossypium hirsutum) long-term continuous cropping soils were examined. Four cropping patterns were established, including one continuous cropping pattern and three crop rotation patterns, and the diversity of the soil microecological community was measured using high-throughput sequencing. The physical and chemical properties of different models of soil were measured, and the soil aggregate structure was determined by dry and wet sieving. Planting of aftercrop tomato and corn altered the bacterial community of the cotton continuous soil to a lesser extent and the fungal community to a greater extent. In addition, continuous cropping reduced the diversity and richness of the soil fungal community. Different aftercrop planting patterns showed that there were very high contents of soil organic carbon and organic matter in the cotton-maize rotation model, while the soil aggregate structure was the most stable in the corn-cotton rotation model. Planting tomato in continuous cropping cotton fields has a greater effect on the soil microbial community than planting maize. Therefore, according to the characteristics of different succeeding crop planting patterns, the damage of continuous cropping of cotton to the soil microenvironment can be alleviated directionally, which will enable the 删除[韩岩 18899126232 [2]]: 删除[韩岩 18899126232 [2]]: rotated 删除[韩岩 18899126232]: The soil bacterial community of different aftercrop rotations was greatly affected by the previous cotton continuous cropping, while the soil fungal community was less affected by the previous cotton continuous cropping. 删除[韩岩 18899126232]:sustainable development of cotton production.